Penguatan Literasi Etika Pemanfaatan Artificial Intelligence sebagai Asisten Riset Tanpa Plagiarisme bagi Mahasiswa - Nur Asitah; Hadi Ismanto; Fatkul Anam; Ahmad Khoir Alhaq; Achmad Mufliq; Rizky Aditya Nugroho; Achmad Wahyudi (Universitas Nahdlatul Ulama Sidoarjo, 2026)
The development of Artificial Intelligence (AI) in higher education opens up opportunities for students to support learning, academic writing, and research. However, the use of generative AI also raises ethical issues, particularly plagiarism, information validity, technological dependency, and academic responsibility. This community service activity aims to strengthen students' ethical literacy in using AI as a research assistant without violating scientific integrity. The activity method uses an educational-participatory approach through academic seminars, interactive discussions, and reflections on AI use practices. The activity was attended by 80 students from various study programs at Nahdlatul Ulama University, Sidoarjo. The material covered the development of AI in Society 5.0, the use of GenAI in higher education, the role of AI as a research assistant, and the ethical boundaries of academic writing. The activity results showed an increase in participants' understanding of the use of AI for brainstorming, topic mapping, outlining, language improvement, and literature summarization while still emphasizing verification, citation, transparency, and academic integrity. This activity encourages the critical, responsible, and plagiarism-free use of AI on campus.